2020
DOI: 10.1039/c9nj05895h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dye removal and separation based on graphene oxide nanomaterials

Abstract: Different graphene-based nanomaterials were synthesized and tested for dye removal, showing that graphene oxide demonstrates high capability for the separation of cationic and anionic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…In addition, the oxygenated functional groups could be effective at potential adsorption [45]. Furthermore, heteroatom-doped graphene shows an improved adsorption performance due to the surface modification [46,47]. As displayed in Figure 9, the synthesized NBG demonstrated 44.1% dye removal in dark conditions, while the NPBG exhibited a higher removal percentage of dye (60.2%) due to its higher surface area.…”
Section: Photocatalytic Studymentioning
confidence: 98%
“…In addition, the oxygenated functional groups could be effective at potential adsorption [45]. Furthermore, heteroatom-doped graphene shows an improved adsorption performance due to the surface modification [46,47]. As displayed in Figure 9, the synthesized NBG demonstrated 44.1% dye removal in dark conditions, while the NPBG exhibited a higher removal percentage of dye (60.2%) due to its higher surface area.…”
Section: Photocatalytic Studymentioning
confidence: 98%
“…These peaks might be labeled as C=C (284.6 eV), C–C (285.5 eV), C–O (286.6 eV), C=O (287.6 eV), and O=C–O (288.8 eV) [ 90 ]. The C1s spectrum of GO was significantly different from graphite, which indicated that the drastic change in the structure was due to the introduction of oxygen functional groups [ 4 ]. On comparing the C1s spectra of GO and IC-rGO, it was evident that the quantity of oxygen functional groups was significantly decreased [ 78 ].…”
Section: Surface Characterization Of 3d Graphene-based Nanomateriamentioning
confidence: 99%
“…[ 3 ]. Due to these attributes, a number of graphene-based nanomaterials have been developed for utilization in energy storage, catalysis, electronic devices, and sensor applications [ 4 , 5 , 6 , 7 , 8 , 9 ]. Recently, graphene-based nanomaterials have also been utilized for aluminum ion batteries as a promising electrode material along with Al-foil in an ionic liquid electrolyte [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in nanoscience and nanotechnology provides a convenient solution to many challenges in diverse fields, with new materials such as 2D materials, [ 1 ] metal catalysts, [ 2 ] organic polymers, [ 3 ] etc., offering unique possibilities in such directions. [ 4 ] Yet, such materials generally lack self‐motion performance for, i.e., targeted drug delivery, which hamper their effectiveness.…”
Section: Introductionmentioning
confidence: 99%